2019
DOI: 10.5209/rlog.62942
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias fonológicas entre síndromes del neurodesarrollo: evidencias a partir de los procesos de simplificación fonológica más frecuentes

Abstract: Los trastornos del neurodesarrollo presentes en alteraciones como el síndrome de Down, el síndrome de Williams y el síndrome de Smith Magenis subyacen en las características cognitivas, conductuales y lingüísticas de quienes los padecen. Pese a tratarse de tres alteraciones genéticas que cursan con discapacidad intelectual y que comparten aspectos de su fenotipo, las investigaciones demuestran que cada síndrome presenta diferentes perfiles lingüísticos. En lo que respecta a las habilidades fonético-fonológicas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…These results were consistent with research reviewed by Stoel-Gammon (2001). A high frequency of substitution and syllable structure processes appears to be a characteristic of DS compared to other neurodevelopmental genetic disorders (Barnes et al, 2009;Hidalgo de la Guía and Garayzábal, 2019). A relative low proportion of Addition processes in Down syndrome had been previously reported by Van Borsel (1996), which could be explained by reduced short-term memory span.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results were consistent with research reviewed by Stoel-Gammon (2001). A high frequency of substitution and syllable structure processes appears to be a characteristic of DS compared to other neurodevelopmental genetic disorders (Barnes et al, 2009;Hidalgo de la Guía and Garayzábal, 2019). A relative low proportion of Addition processes in Down syndrome had been previously reported by Van Borsel (1996), which could be explained by reduced short-term memory span.…”
Section: Discussionsupporting
confidence: 90%
“…Assessments of phonological development in DS populations are mainly based on two elicitation methods: tests of articulation (Dodd, 1976;Van Borsel, 1988, 1996Roberts et al, 2005;Rupela et al, 2010); spontaneous or connected speech (Stoel-Gammon, 1980;Barnes et al, 2009); and sometimes on a combination of both an articulation test and spontaneous speech (Sommers et al, 1988;Parsons and Iacono, 1992;Yousif, 2018;Hidalgo de la Guía and Garayzábal, 2019). Studies indicate a higher frequency of phonological processes in connected speech, but only Yousif (2018) reports some evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the neurological features described above, it has been shown that the population with SMS also has swallowing difficulties, hypotonia of the velopharyngeal and orofacial muscles (Sonies et al, 1997;Solomon et al, 2002), and alterations in the peripheral nervous system (75% of children with SMS) (Greenberg et al, 1996). Phonological difficulties and many simplification processes related to velopharyngeal hypotonia (distortions affecting velar and, mainly, fricative consonant phonemes) have also been described (Hidalgo and Garayzábal, 2019). Therefore, taking these findings into account, it would seem justified to relate the results of the acoustic analysis of this paper to the neuromotor particularities of SMS.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the individuals with SMS show language disorders that mainly affect production and are focused on the morphosyntactic, pragmatic, and phonetic-phonological levels (Garayzábal Heinze et al, 2011;Lamônica et al, 2012;Garayzábal and Lens, 2013;Wilde et al, 2016). Their phonatory profile and speech features, both children and adults, are dysphonia, high f0, excess vocal muscle stiffness, disfluencies, tachylalia, numerous syllabic simplifications, phoneme omissions, and, in general, a high unintelligibility of utterances (Hidalgo and Garayzábal, 2019;Hidalgo-de la Guía, 2019;Hidalgo-De la Guía et al, 2020).…”
Section: Smith-magenis Syndromementioning
confidence: 99%
“…Neurodevelopmental disorders are related to a specific cognitive profile, which is characterized by moderate intellectual disability , poor working memory, and attention deficit and hyperactivity. Language is delayed and speech disorders continue into adulthood (Udwin et al 2001;Solomon et al 2002;Gropman et al 2006;Garayzábal Heinze et al 2011;Osório et al 2012;Heinze and Lens 2013;Garayzábal et al 2014;Hidalgo and Garayzábal 2019). Concerning the behavioral phenotype, individuals with SMS tend to easily show states of anxiety and nervousness, especially in new situations.…”
Section: Introductionmentioning
confidence: 99%